Mobile electrified plants for decentralized wasted gas valorization: A solution to face the challenges of the new energy era. (1st June 2023) - Delikonstantis, Evangelos; Papaioannou, Ioannis; Van Geem, Kevin M.; Stefanidis, Georgios D.
Graphical abstract: Highlights: Electrified mobile plant for offshore valorization of wasted natural gas to olefins. Nanosecond pulsed plasma reactors for gas conversion to acetylene and ethylene. Capital-intensive process rather than energy-intensive; total cost: 1439 USD/tonC2. Gas-to-Olefins is economically and technically more favorable than Gas-to-Liquids. Abstract: In view of the current energy crisis, there is a pressing need for cautious management and exploitation of decentralized natural gas. At present, >120 Bm 3 are flared upstream. Mobile electrified mini-plants, employing state-of-the-art plasma reactors hold promise for such application. Herein, we demonstrate for the first time the technical and economic feasibility of a mobile and electrified process for offshore conversion of currently wasted natural gas streams into C2 species (olefins). Based on experimental performance data, the process model is developed and optimized with respect to anticipated offshore processing constraints while the process economics, i.e., capital expenditures and total cost are estimated. The process economic feasibility is investigated in the context of a disruptive gas value chain for both the US and European market conditions and different shipping distances. Collectively, the proposed electrified process is a capital-intensive process; a capital investment of 21.8 MUSD is required for the commissioning of a 1-ktonC2 /a throughput mini-plant, and the annual equipment depreciation (expressed per ton of product) accounts for 76% of the total production cost (1439 USD/tonC2 ) when a plant lifetime of 20 years is considered. The electricity cost accounts only for 14% of the total cost. The integration of this mobile electrified process in the conventional gas value chain, i.e., liquefied natural gas (LNG) trading, fosters robustness of the LNG trading business. C2 species instead of LNG could directly be traded and supplied to the customers when the landed LNG prices are well below the breakeven values. As such, the LNG trader could still attain a positive profit margin when the landed prices are below the breakeven point. This hybrid model does offer an effective way to sustain the long-term LNG contracts profitable. The proposed electrified Gas-to-Olefins concept is economically and technically more favorable than Gas-to-Liquids concept and more sustainable than LNG trading for electricity generation.